Pendampingan Pendampingan Pembelajaran Bahasa Inggris Pada Santri Pondok Pesantren Darussalam Sumbersari Sumbersari Kencong Kepung Kediri - M. Firdaus Alwi; Sapri Ali (Jurnal Pengabdian kepada Masyarakat Desa (JPMD), 2021)
This English learning assistance will be carried out in the 2021 academic year and the targets of this activity are male and female students who are also students at Madrasah Tsanawiyah and Madrasah Aliyah. This activity is carried out in order to provide English language insight to students, so that students not only get religious knowledge but also get a stock of English knowledge when they are useful after they graduate. This activity has been carried out for one month by providing basic English materials which include grammar, vocabulary, and conversation. This activity received a good response from the administrators and the students. This shows that they are interested in learning English.